2019
DOI: 10.1017/s0272263119000470
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interplay Between Practice Type and Practice Schedule in a Second Language

Abstract: To investigate the skill transfer and the effects of practice schedules in the learning of second language syntax, 129 intermediate-level English learners were divided into six groups, based on practice format (input vs. output practice) and practice schedule (blocked vs. interleaved vs. hybrid [blocked + interleaved]). Analyses revealed that the learners tested on the skill they had practiced outperformed those who were tested on the nonpracticed skill. This pattern was particularly pronounced in comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 66 publications
1
45
4
Order By: Relevance
“…While the results of a 1‐week delayed posttest showed the advantage of interleaved practice over blocked practice, increasing practice was not significantly better or worse than the other two practice schedules. Another recent study, in contrast, showed that an increasing learning schedule led to significantly better outcomes than either blocked or interleaved practice for L2 learners’ spoken grammar knowledge (Suzuki & Sunada, ), which lends direct support to the desirable difficulty framework. In other words, gradually increasing the practice difficulty to match learners’ skill levels helps induce the appropriate level of difficulty throughout training and facilitates learning.…”
Section: L2 Practice and Difficulty In This Issuementioning
confidence: 93%
See 1 more Smart Citation
“…While the results of a 1‐week delayed posttest showed the advantage of interleaved practice over blocked practice, increasing practice was not significantly better or worse than the other two practice schedules. Another recent study, in contrast, showed that an increasing learning schedule led to significantly better outcomes than either blocked or interleaved practice for L2 learners’ spoken grammar knowledge (Suzuki & Sunada, ), which lends direct support to the desirable difficulty framework. In other words, gradually increasing the practice difficulty to match learners’ skill levels helps induce the appropriate level of difficulty throughout training and facilitates learning.…”
Section: L2 Practice and Difficulty In This Issuementioning
confidence: 93%
“…Nakata and Suzuki (), for instance, pursued this line of work and examined whether spacing differentially affects the learning of semantically related and unrelated lexical sets, and found that semantically unrelated sets benefit more from spacing. Another recent study (Suzuki & Sunada, ) also examined whether blocking, interleaving, and increasing schedules differently affect the learning of comprehension and production skills. They found the advantage of increasing schedule over the blocking and interleaving schedules for measures of production accuracy and comprehension speed (reaction time), but not for measures of production speed or comprehension accuracy.…”
Section: Future Directions Of L2 Practice Researchmentioning
confidence: 99%
“…showed advantages of interleaved practice for L2 grammar acquisition. The benefits of interleaving found in these studies may encourage researchers to further explore interleaving effects in order to arrive at a better understanding of the phenomenon (Suzuki & Sunada, ).…”
Section: Defining and Extending Research Areas For L2 Practicementioning
confidence: 99%
“…Furthermore, Rogers and Leow challenged the validity of our framework by referring to inconsistent findings reported for interleaving effects (Nakata & Suzuki, ; Suzuki & Sunada, ) and distributed practice effects (Kasprowicz et al., ; Li & DeKeyser, ). However, we believe that these inconsistent findings actually support, rather than refute, our framework, because these studies demonstrate how linguistic, learner‐related, and context‐related factors interact with each other to affect L2 acquisition, which is the basic tenet of our framework.…”
Section: Empirical Feasibility: Collecting Snapshots Of Complex Pictumentioning
confidence: 96%
“…However, we believe that these inconsistent findings actually support, rather than refute, our framework, because these studies demonstrate how linguistic, learner‐related, and context‐related factors interact with each other to affect L2 acquisition, which is the basic tenet of our framework. Specifically, Nakata and Suzuki () and Suzuki and Sunada () examined the effects of the increasing schedule (blocked practice followed by interleaved practice) on L2 grammar acquisition. While Suzuki and Sunada found the superiority of the increasing schedule over both blocked and interleaved practice, Nakata and Suzuki failed to do so.…”
Section: Empirical Feasibility: Collecting Snapshots Of Complex Pictumentioning
confidence: 99%